Gut Microbiota Metabolites of Dietary Lignans and Risk of Type 2 Diabetes: A Prospective Investigation in Two Cohorts of U.S. Women - Sun, Qi; Wedick, Nicole M.; Pan, An; Townsend, Mary K.; Cassidy, Aedin; Franke, Adrian A.; Rimm, Eric B.; Hu, Frank B.; van Dam, Rob M. (Diabetes care, 2014)
To examine urinary levels of enterolactone and enterodiol, intestinal microbial metabolites of dietary lignans, in relation to type 2 diabetes (T2D) risk. Urinary concentrations of the lignan metabolites were assayed by liquid chromatography-mass spectrometry among 1,107 T2D and 1,107 control subjects in a nested case-control study conducted in participants from the Nurses' Health Study (NHS) and NHSII. Subjects were free of diabetes, cardiovascular disease, and cancer at urine sample collection in 1995-2001. Incident self-reported T2D cases identified through 2008 were confirmed with a validated questionnaire. In both cohorts, T2D subjects had significantly lower concentrations of both enterolactone and enterodiol than control subjects. After multivariate adjustment for lifestyle and dietary risk factors of T2D, urinary concentrations of enterolactone were significantly associated with a lower risk of T2D (pooled odds ratio [OR] comparing the extreme quartiles 0.62 [95% CI 0.44, 0.88], P for trend = 0.003). Higher urinary concentrations of enterodiol were also marginally significantly associated with a lower T2D risk (pooled OR comparing extreme quartiles 0.67 [95% CI 0.48, 0.96], P for trend = 0.08). When concentrations of both metabolites were combined to reflect total lignan intake, the OR was 0.70 (95% CI 0.53, 0.92) for each SD increment of total lignan metabolites. These results indicate that lignan metabolites, especially enterolactone, are associated with a lower risk of T2D in U.S. women. Further studies are needed to replicate these findings and to explore potential mechanisms underlying the observed association.